Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0231845
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive symptoms among Italian medical students: The multicentre cross-sectional “PRIMES” study

Abstract: Background Four percent of the world's population suffers from depression, which is a major public health issue. Medical students are at risk, as their depressive symptoms (DS) prevalence is reported to be approximately 27% worldwide. Since few data on Italian medical students exist, this study aimed to estimate their DS prevalence and assess risk and protective factors. Methods The PRIMES was a multicentre cross-sectional study performed in 12 Italian medical schools. Questionnaires were self-reported and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
45
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 35 publications
(74 reference statements)
13
45
4
2
Order By: Relevance
“…Our research found a link between not doing sports regularly and noticing symptoms that might had pointed to depression during the course of medical studies. Similar results were obtained by Bert et al who investigated the occurrence of depressive symptoms among medical students in Italy and showed that one of the main risk factors for depression is less than 90 minutes of physical activity weekly [14]. Additionally, lack of time was listed as the main reason for lack of physical activity among medical and nursing students [15].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our research found a link between not doing sports regularly and noticing symptoms that might had pointed to depression during the course of medical studies. Similar results were obtained by Bert et al who investigated the occurrence of depressive symptoms among medical students in Italy and showed that one of the main risk factors for depression is less than 90 minutes of physical activity weekly [14]. Additionally, lack of time was listed as the main reason for lack of physical activity among medical and nursing students [15].…”
Section: Discussionsupporting
confidence: 83%
“…Our research showed a link between not having interests that enable one to relax and noticing symptoms that might had suggested depression during the course of medical studies. Similarly, Bert et al listed having a hobby as a protective factor against depression [14]. Our analysis found that there exists a link between not participating in social gatherings often enough and subjective feeling of depressive symptoms during the course of medical studies.…”
Section: Discussionsupporting
confidence: 61%
“…Young adults have been reported to be more likely to present depression [ 6 , 7 , 25 , 26 ], anxiety [ 6 , 7 , 24 , 25 ] and reduced sleep quality [ 11 ]. Ozamiz-Etxebarria and colleagues suggested that one explanation could be the fact that a section of young people can be university students, which usually report high levels of mental health issues [ 27 , 28 ] and might experience additional stress due to the necessity to adapt their university career [ 9 , 26 ]. Indeed, delays in academic activities due to COVID-19 have been correlated with anxiety [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nestes, a ansiedade se manifesta, entre os participantes, como o transtorno mental mais presente (23.1%), seguido de traços ansiosos e depressivos (11.5%) e de traços depressivos (8.8%) 14,[17][18][19] .…”
Section: Discussionunclassified